Problems of criminal legal forecasting of individual criminal behavior - Mikhail P. Kleymenov (Правоприменение)
The subject of the article is the problem of typical assessments of criminal legal risk by offenders.The purpose of the article is to confirm or refute the hypothesis that the attitude of various persons to the possibility of being punished for violating a criminal prohibition can be typologized, and the probability of being punished depends on the criminal's belonging to the corresponding type.The methodology includes dialectical, comparative legal, sociological, statistical, psychological methods, expert assessments, generalizing indicators.The main results, scope of application. The original criminal-legal aspect of predicting individual criminal behavior consists primarily in determining the probability of a potential criminal being brought to criminal responsibility for a possible offense and being punished. Foresight in this case is individual in the literal sense of the word – its subject is primarily a person who is inclined to commit a crime. The position of the researcher of criminal law forecasting of individual criminal behavior, who is obliged to put himself "in the place" of a socially dangerous person, to understand the nature and process of risk assessment, and to be brought to criminal responsibility, is also original. The attitude of different persons to the possibility of being brought to justice for violating a criminal law prohibition may vary widely, acquire a different character, and have specific features. In this regard, theoretically, we can distinguish the following groups of criminal risk: out of risk (“above the law”); habitual risk; "justified" risk; frivolous risk; emotional risk; situational risk; professional risk. The validity of this typology is confirmed by both empirical experience and materials of criminal-legal and psychological research. Conclusion. The magnitude of the criminal legal risk, of course, should be taken into account in the criminal law policy: both when assessing its purposefulness and effectiveness, and when solving the task of a comprehensive information and analytical support for it.